Total Sulfur and Ash Yield of Tanjung Formation Coal in Sekako, Barito Basin, Central Kalimantan: Implication of Depositional Process - Hendra Amijaya; Beny Wiranata; Ferian Anggara; Agung Rizki Perdana; Oyinta Fatma Isnadiyati; Deddy Nan Setya Putra Tanggara (Journal of Applied Geology, 2020)
Tanjung Formation is one of the major coal-bearing deposit in the Barito Basin, Central Kalimantan. The distribution of total sulfur and ash yield in coal is closely related to the depositional environment. This study was to determine the total sulfur and ash yield and the interpretation of the dynamics of depositional process. Coal seam A and B generally have low to medium ash yield 2.82 to 9.23 (wt.%, db) and low total sulfur content of <1 (wt.%, db), except for the 6PLY1 coal sample which has total sulfur content that relatively high at 1.55 (wt.%, db). Coal samples 5PLY1A, 5PLY1B, 5PLY3, 5PLY5, 6PLY2, 6PLY4, 6PLY5, 6PLY7, and 6PLY9 which have low to medium ash yield and low total sulfur content <1% (wt.%, db) are formed in the topogeneous mire (freshwater swamp) in a fluvial environment. The total sulfur content was interpreted to be derived mainly from the parent plant materials. Meanwhile, the 6PLY1 coal sample which has an ash yield of 5.83 (wt.%, db) and total sulfur content of 1.55 (wt.%, db) formed in topogeneous mire in an environment that is invaded by sea water, and the total sulfur content were interpreted coming from the parent plant materials and the effect of seawater invasion which is rich in sulfate (SO4) compounds. It is also supported by the occurrence of syngenetic mineral content (framboidal pyrite) and epigenetic pyrite of 1.23 (vol.%).